Complex formation and stability of westiellamide derivatives with copper(II) - Comba, Peter; Dovalil, Nina; Haberhauer, Gebhard; Hanson, Graeme R.; Kato, Yuki; Taura, Toshiaki (Journal of biological inorganic chemistry, 2010)
The CuII coordination chemistry of three synthetic analogues of westiellamide (H3Lwa) with an [18]azacrown-6 macrocyclic structure and imidazole (H3L1), oxazole (H3L2), or thiazole (H3L3) heterocyclic donors in addition to the peptide groups, is reported. The Nheterocycle-Npeptide-Nheterocycle binding sites are highly preorganized for the coordination to CuII ions. The stability constants of mono- and dinuclear CuII complexes of H3L1, H3L2, and H3L3, obtained by isothermal titration microcalorimetry, are reported. EPR and NMR spectroscopy as well as electrospray ionization mass spectrometry (ESI-MS) were used to characterize the complexes formed in solution. The stabilities of the mononuclear and dinuclear CuII complexes of the three ligands are in the range of 105 M−1, but there are subtle differences; specifically the oxazole-derived ligand has, in contrast to the other two macrocycles, a negative formation entropy for coordination to the first CuII ion and a higher stability for complexation to a second CuII center in comparison with the first CuII center (cooperativity). Differences between the three ligands are also apparent in terms of the formation mechanism. With the oxazole-based ligand H3L2, NMR spectroscopy, EPR spectroscopy, and ESI-MS indicate the formation of a ligand-CuII 2:1 intermediate, and this may explain the differences in the formation entropy as well as the cooperativity.
Gesehen am 10.05.2023